2015
DOI: 10.1016/j.mayocp.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Stone Composition Among First-Time Symptomatic Kidney Stone Formers in the Community

Abstract: Objective To determine the variation in kidney stone composition and its relationship to risk factors and recurrence among first-time stone formers in the general population. Patients and Methods Medical records were manually reviewed and validated for symptomatic kidney stone episodes among Olmsted County, Minnesota residents from January 1, 1984 to December 31, 2012. Clinical and laboratory characteristics and the risk of symptomatic recurrence were compared between stone compositions. Results There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 35 publications
2
74
0
2
Order By: Relevance
“…Given that CaOx is the most common stone type 8,9 and that most first time stones are CaOx, 10 it is likely that most stones in our study were CaOx. Furthermore, in a validation study of stone formers in these cohorts using medical records, 77% of NHS I, 79% of NHS II, and 85% of HPFS stones were at least 50% calcium stones.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Given that CaOx is the most common stone type 8,9 and that most first time stones are CaOx, 10 it is likely that most stones in our study were CaOx. Furthermore, in a validation study of stone formers in these cohorts using medical records, 77% of NHS I, 79% of NHS II, and 85% of HPFS stones were at least 50% calcium stones.…”
Section: Discussionmentioning
confidence: 91%
“…7 For this present study, we do not have stone composition reports for most participants, though it is expected that the majority of stones were CaOx. 811 Although it is likely that less than 10% of stones were 100% UA 10,11 , we analyzed UA supersaturation for this study for completeness, but given the low percentage, these results should be interpreted with caution.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium oxalate kidney stones are more common in men [2, 3], although this gender gap is declining as kidney stones are being diagnosed more often in women [10]. Higher ambient temperature and sunlight indices are independently related to stone prevalence, indicating that geography and environment play a role in kidney stone risk [23].…”
Section: Epidemiology and Risk Factors For Calcium Oxalate Stone Formmentioning
confidence: 99%
“…The most common type of kidney stone is composed of calcium oxalate [2, 3] (Table 1). Calcium oxalate stones are often recurrent, with a 10 year recurrence rate of 30% in first time stone formers [2]. The relationship of calcium oxalate kidney stones to important co-morbidities such as chronic kidney disease and metabolic syndrome is currently unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the older age of stone formers who present with uric acid stones compared to other stone types. 17 It is worth noting, however, that prior studies have suggested that uric acid stones are disproportionately associated with abnormal kidney function or CKD. 2,1820 In a recent study, uric acid stones were associated with more collecting duct plugs than calcium oxalate stones and collecting duct plugs may contribute to kidney dysfunction.…”
Section: Discussionmentioning
confidence: 99%